Characterization of bacteria isolated from rumen substrates of goat (Capra aegagrus hircus) - Odeyemi, A. T.; Oluwole, O. A.; Oso, M. O. (African Journal of Biological Sciences, 2020)
Studies on microorganisms associated with rumen substrates of goat (Capra aegagrus hircus) were done through aerobic and anaerobic fermentation for a period of 12 days. Microscopic, biochemical and molecular identification were carried out. Also proximate values of the substrates over the period of fermentation were analyzed. Seven (7) aerobic bacteria species were isolated, viz.; Bacillus spp, Escherichia coli, Lactobacillus spp, Proteus spp, Pseudomonas spp, Staphylococcus spp, and Serratia spp, with Pseudomonas spp having the highest percentage of occurrence of 30.7%, followed by Bacillus spp (23.7%), followed by Lactobacillus spp, Shigella spp, Proteus spp, Staphylococcus spp, having occurrence of 7.6% each. Also, five (5) anaerobic bacteria were also isolated of which Pseudomonas spp was dominant with 33.3%, Bacillus spp and Lactobacillus spp had occurrence of 25%, Serratia spp, Escherichia spp had least occurrence of 8.3% each. There was increase in some vital proximate values due to the biodegradability nature of the rumen normal flora for the period of fermentation. As a result of this, two bacterial isolates (aerobic and anaerobic) which recorded the highest microbial load and mineral level on the 12th day were characterized by sequence analysis of 16S ribosomal RNA gene. The aerobic isolate was discovered to be 99% identical to Bacillus anthracis CGS-1 strain while the anaerobic isolate was identified as Pseudomonas aeruginosa N17.35 strain. The importance of the characterized microbes in improving the proximate value of utilized fermented rumen content is discussed.
Keywords: Rumen substrates, Goat, Aerobic bacteria, Fermentation, 16S ribosomal RNA.